TEKNOLOGI PENGAWETAN RAMAH LINGKUNGAN UNTUK PENGERAJIN BAMBU TRADISIONAL BERORIENTASI EKSPOR DI DESA BELEGA GIANYAR - Negara, I.M.S.; Simpen, I.N.; Sasmita, G.M.A. (Buletin Udayana Mengabdi; Vol 16 No 3 (2017), 2017)
The objectives of this activity of technology for the Community (IbM) are (1) produced durable bamboo environmentally benign (biodegradable) as the raw material of bamboo handicraft export-oriented by gravity technique in partner Setiana Bamboo Furniture and (2) improve the quality and output quality bamboo handicraft to be compete at the local, national and international market, so that continuity can be maintained and industrial partners would also be increased revenue bamboo craftsmen. To attain those objectives, quality improvement and product quality bamboo handicraft result attacked by the beetles of powder, the raw material craft need to be preserved prior to the process of further use preservatives chitosan, which is insulated from shrimp shell of seafood restaurants waste. It was conducted by replacing fluids (starch) which is favored by the beetles of powder with the solution of chitosan. The results of implementation of IbM, partners currently have a preservation tool by gravity technique relatively easily and quickly as well as with chitosan preservative which is safe and environmentally benign and its solution can be collected again for reuse. In general, the problems before implementation IbM, can be resolved.